Investigation of Sports Commitment, Anxiety of Contagion to Corona Virus and Perceived Stress in University Athletes - Yener Aksoy, Lale Aras, Osman Imamoğlu, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study is to investigate sports commitment, anxiety about catching the corona virus and perceived stress in athletes who are studying at university. Methods:The data of 581 university students studying in different faculties of Ondokuz Mayıs University and competing in one of the individual and team sports as competitors were evaluated. In the study, the scales of commitment to sports, perceived stress and anxiety about catching the corona virus were used. Results: While the individual anxiety sub-dimension and the total score of anxiety about catching the corona virus were significantly different according to gender (p<0.001), socialization anxiety was found to be similar (p>0.05). There was no statistically significant difference in perceived stress scores according to gender (p>0.05). A significant difference was found between the scores of commitment to sports according to gender, the sub-dimension of being fit, dedication and internalization, and the total score of commitment to sports (p<0.05 and p<0.001). While there was a significant difference in the anxiety of catching the corona virus according to the team and individual sports status (p<0.05 and p<0.001), there was no statistically significant difference in the socialization anxiety scores (p>0.05). Conclusion: It has been determined that while the anxiety of catching the corona virus and the state of commitment to sports change according to the gender variable, the perceived stress levels are similar in the university students who compete as individual and team athletes. In order to reduce students' anxiety about catching the corona virus, it may be recommended to take measures to reduce contact in training.